Strategi Peningkatan Hasil PISA Level 2 berbasis Analisis Kesalahan Change and Relationships Siswa SMP - Husriani Husain; St. Nur Khalifah Ali; Abdul Rahman; Bernard Bernard (Mandalika Mathematics and Educations Journal, 2026)
Indonesian students' mathematical literacy in PISA assessments remains low,particularly in the Change and Relationships content area. Most existing studies are quantitative and therefore have not revealed the cognitive processes underlying student errors. This study aims to analyze errors and problem-solving strategies of eighth-grade students in solving PISA Change and Relationships Level 2 problems using the PISA mathematical literacy framework (formulate–employ–interpret). A qualitative case study approach was employed,involving 15 eighth-grade students from SMP Al Wildan Islamic School 22 Makassar. The test instrument consisted of three PISA Level 2 tasks with contexts of goods pricing, intravenous drip rate,and currency exchange. Six students were selected through purposive sampling for in-depth interviews. Data were collected through diagnostic tests, semi-structured interviews,and documentation of student work,then analyzed using source triangulation. Results show that average answer accuracy is only 44.4%,with three consistently identified error categories: representation and modeling errors at the formulate stage, procedural errors at the employ stage,and absent result verification habits at the interpret stage. Successful students demonstrate relational understanding and strong metacognitive awareness. This study contributes a specific error mapping per PISA mathematical literacy stage for Change and Relationships Level 2 content,along with operationally distinct intervention recommendations for each error category